REGIONAL AUTONOMY POLICY MODEL BASED ON FULFILLING REGIONAL AND REGIONAL NEEDS IN EAST KALIMANTAN - Yulianingrum, Aullia Vivi; Elviandri, Elviandri; Aidil, Aidil; Zen, Hafied (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to; first, identify the problems and needs of the East Kalimantan Province in an effort to implement regional autonomy. Second, to formulate a regional autonomy policy model based on the fulfillment of regional and territorial needs in East Kalimantan Province. The research method used is sociological legal research (empirical juridical). Where the research location is at the East Kalimantan Provincial Government office and the East Kalimantan Provincial DPRD located in Samarinda city. The types and sources of data used are primary data and secondary data. The primary data collection techniques are interviews and public discussion forums or FGDs with related apparatus. Literature study to complement secondary data and data analysis in this study is classified as qualitative with deductive inference. The impact of the implementation of regional autonomy has an impact on the determination of regional policies in responding to all the problems that arise so that a regional autonomy implementation strategy is needed in accordance with the needs of the region and the conditions of the region. Regional autonomy must be in accordance with regional needs so that it has an impact on regional independence, community welfare, justice in terms of natural resource management, regional financial capacity and environmental damage, democracy and upholding human rights in accordance with the constitution and equity in terms of economy and infrastructure.